CONSTRUCTION OF SOCIAL REALITY AS THOUGHT MOVEMENT (Theoretical Review On Social Construction of Reality Peter L. Berger) - nfn Karman (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
The concept of constructivism/constructionism is vague but very influential to knowledge. The thoughts in line with it are social construction of reality, social constructionism, social constructionist, social constructivism, social constructivist. Simply, they’re called social construction or coconstruction. One model of this theory is the one introduced by Peter L. Berger and Thomas Luckmann. This theory was also known as dialectic theory. Hence, this article will discuss about the main idea or thought of Peter L. Berger. The main ideas are society as objective and subjective reality. This article also presents limitedness of this theory and criticism against it.Keywords : social construction of reality theory; Peter L. Berger; constructivism; constructionism; coconstruction.